[RE]PLACE - AN INTERVENTION PROPOSAL TO BEMPOSTA - Ivan Fernandes Geraldes; Alexandra Maria Barros Alves Chaves Silva Vidal Saraiva (European Scientific Journal, ESJ, 2015)
This paper addresses the problems of rural development in Portugal, especially in the north-east, and specifically in Bemposta, in Mogadouro. Therefore, it is necessary to explore the role that architecture has been playing in the rehabilitation and conversion of uses as an intervention tool in depopulated rural centers. It is in this context that the re-place term acquires greater importance, functioning as a set of approaches in rural areas, enabling the reuse of old structures, reusing the existing materiality and, thus, seeking a less invasive approach in the existing building - the ruin - respecting the past and its historical and social value. This article was elaborated from a wider research that coincided with my master’s thesis, held at Lusíada University of Porto, under the theme “[RE] PLACE: USANDO A MATÉRIA DO LUGAR - Bemposta”, guided by Professor Alexandra Maria Saraiva, in 2013|2014. The conversion uses emerges as a highly important instrument for the maintenance of the place memory. It is important to highlight the multi functionality of rural areas, recognizing the potential of their resources as strategic elements for promoting balanced and integrated territorial development. The proposed project translates into an intervention that focuses on the reuse of local architecture and targeted for tourism in rural areas (TER), along with the Cultural, interpretive and Housing Center of Bemposta (CCIHB).